2015
DOI: 10.1210/en.2014-1762
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Control of the Female Reproductive Axis Through Gated Responsiveness of the RFRP-3 System to VIP Signaling

Abstract: Throughout most of the ovulatory cycle, estrogen negative feedback restrains the GnRH neuronal system. Just before ovulation, however, estrogen negative feedback is removed to permit stimulation of the preovulatory GnRH/LH surge (positive feedback) by the circadian clock in the suprachiasmatic nucleus (SCN). The mammalian ortholog of avian gonadotropin-inhibitory hormone, RFamide-related peptide 3 (RFRP-3), participates in the circadian-timed removal of estrogen negative feedback to permit the LH surge. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 65 publications
5
66
0
3
Order By: Relevance
“…17 and activities of the SCN, GnRH, and GnIH neurons are coordinated with ovulation (Gibson et al, 2008). Russo et al (2015) examined the specific neurochemical means by which the SCN controls GnIH activity and explored whether the GnIH system exhibits time-dependent responsiveness to SCN signaling to precisely time the LH surge. They found that GnIH cells in female hamsters receive close appositions from SCN-derived vasoactive intestinal polypeptide (VIP)-ergic terminal fibers.…”
Section: Regulation Of Estrous or Menstrual Cycle In Female Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 and activities of the SCN, GnRH, and GnIH neurons are coordinated with ovulation (Gibson et al, 2008). Russo et al (2015) examined the specific neurochemical means by which the SCN controls GnIH activity and explored whether the GnIH system exhibits time-dependent responsiveness to SCN signaling to precisely time the LH surge. They found that GnIH cells in female hamsters receive close appositions from SCN-derived vasoactive intestinal polypeptide (VIP)-ergic terminal fibers.…”
Section: Regulation Of Estrous or Menstrual Cycle In Female Mammalsmentioning
confidence: 99%
“…Central VIP administration markedly suppresses GnIH cellular activity in the evening, but not the morning (Table 1). However, double-label in situ hybridization for GnIH and the VIP receptors, VPAC1and VPAC2, revealed that the majority of GnIH cells do not co-express either receptor in Syrian hamsters or mice, suggesting that SCN VIP-ergic signaling inhibits GnIH cells indirectly (Russo et al, 2015). MolnĆ”r et al (2011) investigated if GnIH neurons are involved in estrogen feedback signaling in mice.…”
Section: Regulation Of Estrous or Menstrual Cycle In Female Mammalsmentioning
confidence: 99%
“…GnRH neuronal processes, named ā€œdendrons,ā€ by Herbison group [3], form an interwoven network that receives direct synaptic and neuropeptide input from upstream regulatory neurons, most notably kisspeptin [4, 5]. This GnRH network integrates other signals that impinge on reproduction, such as stress [6, 7], endocrine disruptors [8], circadian rhythms [9, 10], metabolism [11, 12], and acute inflammation during infection [13-15]. …”
Section: Introductionmentioning
confidence: 99%
“…However, just prior to ovulation, peak E 2 concentrations act via positiveā€feedback to initiate the LH surge that triggers ovulation . Previous findings by our group and others suggest that the temporary shift from negativeā€ to positiveā€feedback is coordinated by the SCN …”
Section: Introductionmentioning
confidence: 77%